A Novel Small Molecular Inhibitor of DNMT1 Enhances the Antitumor Effect of Radiofrequency Ablation in Lung Squamous Cell Carcinoma Cells - Liu, Yuan-Yuan; Ding, Cheng-Zhi; Chen, Jia-Ling; Wang, Zheng-Shuai; Yang, Bin; Wu, Xiao-Ming (Frontiers in Pharmacology, 2022)
Radiofrequency ablation (RFA) is a relatively new and effective therapeutic strategy for treating lung squamous cell carcinomas (LSCCs). However, RFA is rarely used in the clinic for LSCC which still suffers from a lack of effective comprehensive treatment strategies. In the present work, we investigate iDNMT, a novel small molecular inhibitor of DNMT1 with a unique structure. In clinical LSCC specimens, endogenous DNMT1 was positively associated with methylation rates of miR-27-3p′s promoter. Moreover, endogenous DNMT1 was negatively correlated with miR-27-3p expression which targets PSEN-1, the catalytic subunit of γ-secretase, which mediates the cleavage and activation of the Notch pathway. We found that DNMT1 increased activation of the Notch pathway in clinical LSCC samples while downregulating miR-27-3p expression and hypermethylation of miR-27-3p′s promoter. In addition of inhibiting activation of the Notch pathway by repressing methylation of the miR-27-3p promoter, treatment of LSCC cells with iDNMT1 also enhanced the sensitivity of LSCC tumor tissues to RFA treatment. These data suggest that iDNMT-induced inhibition of DNMT-1 enhances miR-27-3p expression in LSCC to inhibit activation of the Notch pathway. Furthermore, the combination of iDNMT and RFA may be a promising therapeutic strategy for LSCC.